MENGGALI POTENSI KEWIRAUSAHAAN LOKAL INOVASI BERBASIS KEARIFAN LOKAL - Hanafiah Hanafiah; Aman Nulhaqim; Ade Nurpriatna; Rika Opsari Pusparini S (LPPM Universitas Bina Bangsa, 2024)
Entrepreneurship as a concept includes innovation, risk management and resource management to create value. Local entrepreneurship is an important aspect in mapping regional economic potential, which is closely related to local wisdom, cultural values and community needs. This needs to be explored and developed. The aim of this workshop is to determine students' entrepreneurial potential, increase entrepreneurial knowledge and skills, and plan special activities to establish and develop local companies. This workshop consists of three sessions which include presentations, group discussions, case studies and simulations. The results of the workshop were the identification of local business opportunities, increased skills of participants and a spirit of cooperation between local communities. The workshop produced various outputs, such as business plans, new networks, skills development and training materials that support the development of local entrepreneurship. In conclusion, this workshop not only helps explore local entrepreneurial potential, but also strengthens the skills and cooperation of the participants, which is an important step in developing local entrepreneurship and encouraging regional economic growth